The Development of Science Learning Tools with the SSCS Model Integrated with Islamic Values to Improve Critical Thinking Skills - Fadhliyatul Ulya; Masturi Masturi; Partaya Partaya (Universitas Negeri Semarang, 2023)
The implementation of the revised 2013 Curriculum requires the establishment of religious character and supports students to have 4C skills which include critical thinking, creativity, collaboration and communication. The previous study shows that there is a need to increase students' 4C skills. The integration of Islamic values has not been fully carried out in the learning process. This study aims to analyze the effectiveness of science learning tools to improve students' critical thinking skills. The research method used is Research and Development (R and D) with a 4-D model (Define, Design, Develop and Disseminate). The subjects of this study were students in class VIII B and VIII C at Junior high school MTsN 1 Semarang. The data collection techniques used are observation, interviews, questionnaires and tests. The result of the N-Gain score for critical thinking skills is 0.34 which is in the moderate category. The average results of the self-regulation questionnaire for the experimental class are 2.76 and 2.74 for the control class, both of them are in the very good category. Based on the results of this study, the science learning tool with the SSCS model integrated with Islamic values is effective for improving critical thinking skills.